Closing the gender gap in pensions. A microsimulation analysis of the Norwegian NDC pension system - Elin Halvorsen; Axel West Pedersen (Statistics Norway, Research Department, 2017)
In this paper we use an advanced micro-simulation model to study the distributional effects of the reformed Norwegian pension system with a particular focus on gender equality. The reformed Norwegian system is based on the NDC-formula with fixed contribution/accrual rates over the active life-phase and with accumulated pension wealth being transformed into an annuity upon retirement. A number of redistributive components are built into the system that makes it deviate from complete actuarial fairness: a unisex annuity divisor, a ceiling on annual earnings, generous child credits, a possibility for widows/widowers to inherit pension rights from a deceased spouse, a targeted guarantee pensions with higher benefit rates to single pensioners compared to married/cohabitating pensioners, and finally the tax system that is particularly progressive in its treatment of pensioners and pension income. Taking complete actuarial fairness as the point of departure, we conduct a stepwise analysis to investigate how these different components of the National Insurance pension system impact on the gender gap in pensions and on inequality in the distribution of pension income within a cohort of pensioners.
Keywords: D31; E47; H55; 330; Pensions; Gender gap; Inequality; Micro simulation